1980
DOI: 10.1136/thx.35.11.833
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma in Rhodesian Africans.

Abstract: The prevalence of asthma in a small African town has been assessed using two questionnaires. The first was put to 9768 subjects aged 5 years and older and the second, more detailed, questionnaire to random selections of these subjects grouped according to their replies. The overall prevalence of asthma was 1-40%. In those under 20 years of age it was 1-20% and in adults, 1-57%. This adult rate is similar to those in developed countries but that in children is lower. The relative paucity of childhood asthma is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The overall prevalence of asthma was 1.40%, ranging between 1.20% in those under 20 years of age and 1.57% in adults 2. Similar results were obtained in another study that analyzed the prevalence of childhood asthma in Southern Africa, in 1977 3.…”
Section: Prevalence Rates Of Respiratory Allergic Diseasessupporting
confidence: 82%
“…The overall prevalence of asthma was 1.40%, ranging between 1.20% in those under 20 years of age and 1.57% in adults 2. Similar results were obtained in another study that analyzed the prevalence of childhood asthma in Southern Africa, in 1977 3.…”
Section: Prevalence Rates Of Respiratory Allergic Diseasessupporting
confidence: 82%
“…The high burden of infectious diseases and particularly tuberculosis, AIDS and malaria in Sub‐Saharan African countries where resources are scarce, has meant that asthma has not been considered as a health priority by governments, research funders and researchers. In addition, previous studies in Africa (1–11), based on limited and noncomparable methods, have generally indicated that asthma prevalence was relatively low in the majority of countries. The first random population survey conducted in adults using the same methodology within several centres in Europe and two centres in developing countries (Bombay and Algeria) showed large variation of asthma prevalence with the highest prevalence in industrialized countries.…”
mentioning
confidence: 99%
“…[8] One of the first prevalence studies on asthma in Africa was a questionnaire-based study performed in Rhodesia (now Zimbabwe) in 1975, where symptoms were assessed in 9 287 participants older than 5 years. [9] Asthma prevalence of 1.6% in adults was similar to that of high-income countries (HICs) but was lower in children and adolescents <20 years, at 1.2%. The authors hypothesised that the relative rarity of childhood asthma was due to a protective effect by parasitic infestation.…”
mentioning
confidence: 77%